Preoperative hepatic artery embolization before distal pancreatectomy plus celiac axis resection does not improve surgical results: A Spanish multicentre study. Issue 5 (October 2021) - Ramia, Jose M.; de Vicente, Emilio; Pardo, Fernando; Sabater, Luis; Lopez-Ben, Santiago; Quijano M, Yolanda; Villegas, Trinidad; Blanco-Fernandez, Gerardo; Diez-Valladares, Luis; Lopez-Rojo, Irene; Martin-Perez, Elena; Pereira, Fernando; et al.
Abstract: Background: Distal pancreatectomy with celiac axis resection (DP-CAR) is a surgical procedure with high morbidity and mortality performed in patients with locally advanced pancreatic cancer. Preoperative embolization of hepatic artery (PHAE) has been postulated as a technical option to increase resection rate. Objective: comparison of morbidity and mortality at 90 days, operative time, hospital stay and survival between patients that performed DP-CAR with and without PHAE. Methods: Observational retrospective multicentre study. Inclusion criteria: patient operated in Spanish centers with DP-CAR for pancreatic cancer from April 2004 until 23 June 2018. Preoperative (PHAE, neodjuvant treatment), intraoperative (operative time and blood loss) and postoperative data (morbidity, hospital stay, R0 and survival) were studied. Complications were measured with Clavien classification at 90 days. Specific pancreatic complications were measured using ISGPS classifications. Data were analyzed using R version 3.1.3 (http://www.r-project.org ). Level of significance was set at 0.05. Results: 41 patients were studied. 26 patients were not embolized (NO-PHAE group) and 15 patients received PHAE. Preoperative BMI and percentage of neoadjuvant chemotherapy were the only preoperative variables different between both groups. The operative time in the PHAE group was shorter (343 min) than in the non-PHAE group (411 min) (p < 0.06). Major morbidity (Clavien > IIIa) and mortality at 90 days were higher in the PHAE group than in the non-PHAE group (60% vs 23% and 26.6% vs 11.6% respectively) (p < 0.004). No statistical difference in overall survival was observed between both groups (p = 0.14). Conclusion: In our study PHAE is not related with less postoperative morbidity. Even more, major morbidity (Clavien III-IV) and mortality was higher in PHAE group. Highlights: Embolization of hepatic artery (PHAE) is frequently performed before DP-CAR. We have compared two groups of patients (PHAE and non-PHAE groups). The operative time in the PHAE group was shorter than in the non-PHAE group. Major morbidity and mortality at 90 days were higher in the PHAE group. No statistical difference in overall survival was observed between both groups.